Pengaruh Harga dan Fasilitas Terhadap Kepuasan Pelanggan Pada Hotel Gading Beach Kabupaten Sikka - Emiliana Constantina; Yoseph Darius P. Rangga; Yohanes Jibrail Mado (Program Studi Kewirausahaan Universitas Nusa Nipa Indonesia, 2024)
The objective of this study was to ascertain the influence of price and facilities on customer satisfaction. The population under investigation comprised customers who had stayed at the Gading Beach hotel. Given the absence of any limiting factors, a sample of 83 individuals was selected. Data were gathered through questionnaires and analysed using descriptive inferential methods, specifically multiple linear regression. Hypothesis testing was conducted through the F-test and t-test. The results of the descriptive analysis indicate that the price and facility variables are classified as unsatisfactory, whereas the customer satisfaction variable is classified as satisfactory. The results of the t-test statistics indicate that the price and facility variables exert a partial influence on customer satisfaction. The results of the F-test statistics indicate that, when considered collectively, all independent variables exert a significant influence on customer satisfaction. The results of the determination analisys demonstrate that the price and facilities variables contribute 37.5% to customer satisfaction at Gading Beach Hotel, Sikka Regency. The remaining 62.5% is influenced by factors outside the scope of the research variables.